Dosage calculations - Pickar, Gloria D.; Amy Pickar Abernethy (Clifton Park, New York : Delmar Cengage Learning, 2013)
Features the three-step approach to basic and advanced Formula Method calculations that nursing and other health care professionals prefer. Including full-color images of drug labels, critical thinking assessments, and clinical examples, this title gives readers the skills they need to master dosage calculations in any clinical setting.
Section 1. Pretest and Mathematics Review: Fractions and decimals ; Ratios, percents, simple equations, and ratio-proportion -- Section 2. Measurement Systems, Drug Orders, and Drug Labels: Systems of measurement ; Conversions: metric and household systems ; Conversions for other clinical applications: time and temperature ; Equipment used in dosage measurement ; Interpreting drug orders ; Understanding drug labels ; Preventing medication errors -- Sectio 3. Drug Dosage Calculations: Oral dosage of drugs ; Parenteral dosage of drugs ; Reconstitution of solutions ; Pediatric and adult dosages based on body weight ; Alternative dosage calculation methods: ratio-proportion and dimensional analysis -- Section 4. Advanced Calculations: Intravenous solutions, equipment, and calculations ; Body surface area and advanced pediatric calculations ; Advanced adult intravenous calculations -- Essential Skills Evaluation: Posttest: Answer sheet -- Comprehensive Skills Evaluation: Answers -- Appendix A: Study guide -- Appendix B: Apothecary system.
Includes bibliographical references and index.
Keywords: PHARMACEUTICAL ARITHMETIC